Restriction of chronic Escherichia coli urinary tract infection depends upon T cell‐derived interleukin‐17, a deficiency of which predisposes to flagella‐driven bacterial persistence. Issue 11 (9th September 2020) - Chamoun, Michelle N.; Sullivan, Matthew J.; Goh, Kelvin G. K.; Acharya, Dhruba; Ipe, Deepak S.; Katupitiya, Lahiru; Gosling, Dean; Peters, Kate M.; Sweet, Matthew J.; Sester, David P.; Schembri, Mark A.; Ulett, Glen C.
Abstract: Urinary tract infections (UTI) frequently progress to chronicity in infected individuals but the mechanisms of pathogenesis underlying chronic UTI are not well understood. We examined the role of interleukin (IL)‐17A in UTI because this cytokine promotes innate defense against uropathogenic Escherichia coli (UPEC). Analysis of UPEC persistence and pyelonephritis in mice deficient in IL‐17A revealed that UPEC CFT073 caused infection at a rate higher than the multidrug resistant strain EC958. Il17a −/− mice exhibited pyelonephritis with kidney bacterial burdens higher than those of wild‐type (WT) mice. Synthesis of IL‐17A in the bladder reflected a combination of γδ‐T and TH 17 cell responses. Analysis of circulating inflammatory mediators at 24h postinoculation identified predictors of progression to chronicity, including IL‐6 and monocyte chemoattractant protein‐1 (MCP‐1). Histological analysis identified infiltrating populations of neutrophils, NK cells, and γδ T cells in the bladder, whereas neutrophils predominated in the kidney. Analysis of the contribution of flagella to chronicity using hyper‐flagellated and fliC ‐deficient UPEC in WT and Il17a −/− mice revealed that, in a host that is deficient for the production of IL‐17A, flagella contribute to bacterial persistence. These findings show a role for IL‐17A in defense against chronic UTI and a contribution of flagella to the pathogenesis of infection.